A surface-coated modified AlH3 and its processing method and application

By forming a dense inorganic shell layer structure on the surface of AlH3, the problem of insufficient thermal stability of AlH3 in solid propellants is solved, the drug production and energy performance are significantly improved, and the use requirements of high-energy solid propellants are met.

CN116621119BActive Publication Date: 2025-04-18HUBEI INST OF AEROSPACE CHEMOTECHNOLOGY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310613973.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-29
Publication Date
2025-04-18
Estimated Expiration
2043-05-29

AI Technical Summary

Technical Problem

The existing AlH3 materials have insufficient thermal stability in solid propellants, resulting in poor drug production performance and are difficult to meet the use requirements of high-energy solid propellants.

Method used

By using nickel fluoride dispersion as the treatment agent, a dense inorganic shell structure is formed on the surface of AlH3 to enhance its thermal stability. The method includes placing AlH3 in a mixed solvent for wetting pretreatment, and then performing a strengthening reaction using nickel fluoride and a dispersant to form an inorganic shell layer.

Benefits of technology

It significantly improves the thermal stability of AlH3, solves the porosity problem caused by hydrogen release in propellants, realizes stable preparations in butyl hydroxy propellants and nitrate plasticizing propellants, and improves the energy performance of solid propellants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116621119B_ABST
    Figure CN116621119B_ABST
Patent Text Reader

Abstract

The present invention discloses a surface-coated modified AlH3 and a treatment method and application thereof. In the product of the present invention, AlH3 particles are coated with an inorganic shell layer to form a core-shell structure, and the thickness of the inorganic shell layer ranges from 10nm to 60nm; the particle size of the AlH3 particles ranges from 10μm to 90μm. The method is to use a nickel fluoride dispersion as a surface treatment agent, and to construct an AlH3@NiF2 core-shell structure material by reacting nickel fluoride, water, and Al(OH)3, Al2O3, etc. on the surface of AlH3. This method can effectively strengthen the surface structure of AlH3, and the thermal stability of the treated AlH3 is significantly improved compared to that before treatment. It can be used in the application of butyl hydroxy propellant and nitrate plasticized propellant to achieve stable drug formation, and solve the problem of pores caused by hydrogen release of AlH3 in the propellant. The method is simple to operate, green and efficient, easy to industrialize, and can be used for new solid propellants to improve their energy performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid propellants, in particular to a surface-coated modified AlH 3 and its processing methods and applications. Background Art

[0002] AlH 3 The mass hydrogen storage capacity is as high as 10.08%, the average relative molecular mass of the combustion products is small, and the thermal decomposition temperature is relatively high. Replacing Al powder in solid composite propellants can significantly improve their energy performance.

[0003] In the 1940s, American scientist Finholt first used LiH and AlCl 3 AlH was prepared by reaction in ether solution 3 Ether complex; In the 1960s and 1970s, Dow Chemical scientists Turley and Rinn used LiAlH 4 With AlCl 3 Synthesis of AlH 3 The ether complex of AlH 3 The ether complex was deetherified and crystallized to obtain crystallized AlH 3 , to prepare non-solvated AlH 3 And the α-AlH 3 The crystal structure of α-AlH 3 The most common method.

[0004] AlH 3 It is a metastable compound. It will decompose and release hydrogen under heating conditions, directly converting AlH 3 When used in the preparation of solid propellants, it will cause pores or cracks in the propellants, deteriorating the drug properties of the propellants; when used in fuel cells, it will reduce the battery performance. People have been trying to improve AlH 3 thermal stability.

[0005] US Patent No. 3801707 discloses a free radical inhibitor that increases the AlH 3 The thermal stability scheme, that is, in AlH 3 Phenothiazine (PTA), a free radical inhibitor, is added before the conversion crystallization; Chinese patent CN109019507 discloses a fullerene stabilizer to improve AlH 3 Stability solution, namely AlH 3 Add stabilizer to obtain AlH 3 ; U.S. Patent No. 3855022 discloses a nitrocellulose coated AlH 3 Method for improving compatibility; Chinese patent CN108163839 discloses a carbon nanotube coated AlH3 method.

[0006] However, the above treatment of AlH 3 The method has the problems of complex method and easy material shedding, which makes the AlH 3 The material requires harsh conditions in propellant applications and still cannot meet the requirements for the use of high-energy solid propellants. Therefore, it is still necessary to develop new AlH 3 Strategies to improve thermal stability. Summary of the invention

[0007] In order to increase AlH 3 Thermal stability, solving AlH 3 The present invention discloses a surface-coated modified AlH 3 The present invention adopts nickel fluoride dispersion as a treating agent, and uses nickel fluoride, water and AlH 3 Surface Al(OH) 3 、Al 2 O 3 Al compounds react with AlH 3 A dense inorganic shell structure is formed on the surface, thereby achieving AlH 3 Surface strengthening treatment, the preparation mechanism is as follows:

[0008]

[0009] In order to achieve the above-mentioned object of the invention, the method of the present invention is implemented by the following technical scheme: the present invention first provides a surface-coated modified AlH 3 , AlH 3 The particles are coated with an inorganic shell layer to form a core-shell structure, and the thickness of the inorganic shell layer ranges from 10nm to 60nm; the AlH 3 The particle size range is 10 μm to 90 μm; the composition of the inorganic shell layer includes Ni(OH) 2 and Al(OH) 3 F 6 .

[0010] The present invention also provides the above-mentioned surface-coated modified AlH 3 The processing method comprises the following steps:

[0011] S1, AlH 3 Place in a mixed solvent, stir, filter, and dry in vacuum at room temperature;

[0012] S2, mixing the surface treatment agent and the dispersant evenly, stirring, to obtain a surface treatment liquid;

[0013] S3, the AlH treated in step S13 Add the surface treatment solution prepared in step S2, mix well, then filter under reduced pressure, rinse with deionized water and anhydrous ethanol for multiple times, and dry to obtain the surface treated AlH 3 .

[0014] Furthermore, the dispersant in the above step S2 is a mixture of water and one of the following organic solvents: tetrahydrofuran, acetone, acetonitrile, ethanol; and the pH value of the dispersant is between 6 and 8.

[0015] Further, the above dispersant is formulated as follows:

[0016] When it is water / tetrahydrofuran, the volume fraction of water is 30% to 50%;

[0017] When it is water / acetone, the volume fraction of water is 20% to 50%;

[0018] When it is water / acetonitrile, the volume fraction of water is 30% to 50%;

[0019] When it is water / ethanol, the volume fraction of water is 30% to 50%.

[0020] Furthermore, the surface treatment agent in the above step S2 is at least one of nickel fluoride and / or nickel fluoride (II) hydrate; the mixed solvent in the step S1 is a mixture of water and one of tetrahydrofuran, acetone and acetonitrile, and the volume fraction of water is 1% to 10%.

[0021] Furthermore, in the above treatment method, AlH 3 , the mass ratio of surface treatment agent and dispersant is: (50-55) parts: (5-10) parts: (45-35) parts.

[0022] Furthermore, the temperature conditions in the above steps S1 and S2 are both 20°C to 30°C; the stirring speed is controlled at 60 to 400 rpm, and the stirring time is 1 hour; the temperature conditions in the step S3 are both 20°C to 30°C; the stirring speed is controlled at 60 to 400 rpm, and the stirring time is 1.5-3 hours.

[0023] The present invention also provides the above-mentioned surface-coated modified AlH 3 Application in hydroxybutyl solid propellants and nitrate plasticized propellants.

[0024] Furthermore, the above-mentioned HTPB propellant comprises the following components by weight: the surface-coated modified AlH 310 to 20 parts, 4 to 10 parts of dioctyl sebacate, 8 to 12 parts of terminal hydroxy butadiene, 55 to 67 parts of ammonium perchlorate, 0.3 to 0.5 parts of curing agent, and 0.02 to 0.05 parts of curing catalyst; the nitrate plasticizer propellant comprises the following components in parts by weight: the surface-coated modified AlH 3 The invention comprises 10 to 20 parts, 15 to 22.5 parts of a nitrate plasticizer prepared in a mass ratio of NG / and BTTN of 1:1, 5 to 7.5 parts of a polyazide glycidyl ether adhesive, 35 to 45 parts of an explosive, 15 to 20 parts of ammonium perchlorate, 0.3 to 0.5 parts of a curing agent, and 0.02 to 0.05 parts of a curing catalyst.

[0025] Furthermore, the above-mentioned curing agents are at least one of hexamethylene diisocyanate and toluene diisocyanate; the curing catalysts are triphenyl bismuth; and the explosives are at least one of RDX or octogenin.

[0026] The advantages of the present invention compared with the prior art are:

[0027] The first step is to treat AlH 3 Surface wetting pretreatment, followed by dispersant and surface treatment agent in AlH 3 The surface is treated with enhanced reaction and finally AlH 3 A dense inorganic shell structure is formed on the surface, thereby achieving AlH 3 Surface strengthening treatment. The treated AlH 3 The thermal stability of the material is significantly improved compared to that before treatment. It can be stably prepared in the application of butyl hydroxy propellant and nitrate plasticizer propellant, solving the problem of AlH 3 The method is simple to operate, green and efficient, easy to industrialize, and has great potential for improving the energy performance of solid propellants. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] These and / or other aspects and advantages of the present invention will become more clear and easier to understand from the following detailed description of the embodiments of the present invention in conjunction with the accompanying drawings, in which:

[0029] Figure 1 The AlH 3 Schematic diagram of the structure before and after the processing;

[0030] Figure 2 The untreated AlH 3 SEM and EDS images of untreated AlH 3 Figure (B)-(D) is the SEM image of untreated AlH 3EDS diagram of

[0031] Figure 3 The AlH after surface treatment in the embodiment of the present invention 3 SEM and EDS images of AlH after surface treatment; Figure (A) is 3 Figure (B)-(F) shows the SEM images of AlH after surface treatment. 3 EDS diagram of . DETAILED DESCRIPTION

[0032] In order to enable those skilled in the art to better understand the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and specific implementation methods.

[0033] Example 1

[0034] At 20℃~30℃, AlH 3 Place in water / tetrahydrofuran (V 水 :V 四氢呋喃 =1:99) mixed solvent and stirred for 1 hour, the speed was controlled at 60-400 rpm, filtered, and dried under vacuum at room temperature. Add 10 mL of water / ethanol dispersion to a 100 mL beaker, then add 1.0 g of nickel fluoride, stir for 1 hour at 20°C to 30°C, the speed was controlled at 60-400 rpm, and then add 10.0 g of AlH 3 , stirring at a temperature range of 20°C to 30°C for 1.5 to 3 hours, controlling the rotation speed at 60 to 400 rpm to stir the solution evenly; vacuum filtration, rinsing with deionized water 3 times, rinsing with anhydrous ethanol 3 times, and drying in a vacuum oven for 24 hours to obtain the surface-treated AlH 3 . Figure 1 AlH 3 Schematic diagram of the structure before and after the treatment process; AlH 3 The SEM and EDS images are shown in Figure 2 As shown, the AlH without surface treatment 3 The surface is smooth, the particles are dispersed, and the surface elements are composed of Al, C, and O; after treatment, AlH 3 The SEM and EDS images are shown in Figure 3 As shown in the figure, there are granular and film-like objects attached to the surface, and the surface elements are composed of Al, C, O, F, and Ni. Moreover, F and Ni elements are evenly distributed on the surface of the particles, which further indicates that after surface treatment, the surface treatment agent and AlH 3 The surface layer undergoes chemical reactions and in the AlH 3 A layer of inorganic compounds is formed on the surface. The AlH 3 Pressure changes.

[0035] After testing, at 50℃, AlH 3 The pressure changes before and after treatment are shown in Table 1. It can be seen that compared with before treatment, after treatment, AlH 3 The amount of hydrogen released is significantly reduced.

[0036] Table 1 AlH 3 Pressure change table before and after treatment

[0037]

[0038] Untreated AlH 3 and treated AlH 3 Nitrate ester plasticized solid propellants were prepared respectively, and the specific methods were as follows:

[0039] 21.0 g of nitrate plasticizer, 7.50 g of azide glycidyl ether adhesive, 35.00 g of octogen, 16.00 g of ammonium perchlorate, 0.48 g of toluene diisocyanate and 0.02 g of triphenyl bismuth were stirred evenly, and 20.00 g of untreated AlH 3 (obtained propellant number X-1) and treated AlH 3 (The obtained propellant number X-2), after mixing without a paddle, the material was transferred to a polytetrafluoroethylene mold of 80×120×10 mm, vacuum degassed, and then placed in an oven for curing for 7 days to prepare a solid propellant pellet. The results are shown in Table 2.

[0040] Table 2 Drug properties of nitrate plasticized solid propellant

[0041] Propellant No. <![CDATA[AlH 3 ]]> Effect of medicine X-1 <![CDATA[Unprocessed AlH 3 > Lots of pores and cracks inside X-2 <![CDATA[Processed AlH 3 > Well cured, dense and non-porous

[0042] Untreated AlH 3 and surface treated AlH 3 The hydroxybutyl solid propellant is prepared respectively, and the specific method is as follows:

[0043] 10.00 g of hydroxy-terminated butadiene, 63.58 g of ammonium perchlorate, 6.00 g of dioctyl sebacate, 0.40 g of toluene diisocyanate and 0.02 g of triphenyl bismuth were stirred evenly, and 20.00 g of untreated AlH 3 (obtained propellant number X-3) and treated AlH 3 (The obtained propellant number is X-4), after mixing without a paddle, the material was transferred to a polytetrafluoroethylene mold of 80×120×10 mm, vacuum degassed, and then placed in an oven at 50° C. for 7 days to prepare a solid propellant pellet. The results are shown in Table 3.

[0044] Table 3 Drug properties of hydroxybutyrate solid propellant

[0045] Propellant No. <![CDATA[AlH 3 ]]> Effect of medicine X-3 <![CDATA[Unprocessed AlH 3 > Lots of pores and cracks inside X-4 <![CDATA[Processed AlH 3 > Well cured, dense and non-porous

[0046] Example 2

[0047] At 20℃~30℃, AlH 3 Place in water / acetonitrile (V 水 :V 四氢呋喃 =1:99) mixed solvent and stirred for 1 hour, the speed was controlled at 60-400 rpm, filtered, and dried under vacuum at room temperature. Add 10 mL of water / acetonitrile (V = 1:99) to a 100 mL beaker. 水 :V 乙腈 =2:1) ​​dispersion, add 1.9g nickel fluoride, stir for 1 hour at 20℃~30℃, control the speed at 60~400rpm, then add 10.0g AlH 3 , stirring at a temperature range of 20°C to 30°C for 1.5 to 3 hours, controlling the rotation speed at 60 to 400 rpm to stir the solution evenly; vacuum filtration, rinsing with deionized water 3 times, rinsing with anhydrous ethanol 3 times, and drying in a vacuum oven for 24 hours to obtain the surface-treated AlH 3 .

[0048] After testing, at 50℃, AlH 3 The pressure changes before and after treatment are shown in Table 4. It can be seen that increasing the amount of surface strengthening agent will increase the pressure of AlH 3 The amount of hydrogen released further decreased.

[0049] Table 4 AlH 3 Pressure change table before and after treatment

[0050]

[0051] Untreated AlH 3 and surface treated AlH 3 The high-energy solid propellants are prepared separately, and the specific methods are as follows:

[0052] 21.0 g of nitrate plasticizer, 7.50 g of azide glycidyl ether adhesive, 35.00 g of octogen, 16.00 g of ammonium perchlorate, 0.48 g of toluene diisocyanate and 0.02 g of triphenyl bismuth were stirred evenly, and 20 g of untreated AlH 3 (obtained propellant number X-5) and treated AlH 3 (The obtained propellant number is X-6), after mixing without a paddle, the material was transferred to a polytetrafluoroethylene mold of 80×120×10 mm, vacuum degassed, and then placed in an oven at 50° C. for 7 days to prepare a solid propellant pellet. The results are shown in Table 5.

[0053] Table 5 Drug properties of nitrate plasticized solid propellant

[0054] Propellant No. <![CDATA[AlH 3 ]]> Effect of medicine X-5 <![CDATA[Unprocessed AlH 3 > Lots of pores and cracks inside X-6 <![CDATA[Processed AlH 3 > Well cured, dense and non-porous

[0055] Untreated AlH 3 and surface treated AlH 3 The hydroxybutyl solid propellant is prepared respectively, and the specific method is as follows:

[0056] 10.00 g of hydroxy-terminated butadiene, 63.58 g of ammonium perchlorate, 6.00 g of dioctyl sebacate, 0.40 g of toluene diisocyanate and 0.02 g of triphenyl bismuth were stirred evenly, and 20.00 g of untreated AlH 3 (obtained propellant number X-7) and treated AlH 3 (The obtained propellant number is X-8), after mixing without a paddle, the material was transferred to a polytetrafluoroethylene mold of 80×120×10 mm, vacuum degassed, and then placed in an oven at 50° C. for 7 days to prepare a solid propellant pellet. The results are shown in Table 6.

[0057] Table 6 Pharmaceutical properties of hydroxybutyrate solid propellant

[0058] Propellant No. <![CDATA[AlH 3 ]]> Effect of medicine X-7 <![CDATA[Unprocessed AlH 3 > Lots of pores and cracks inside X-8 <![CDATA[Processed AlH 3 > Well cured, dense and non-porous

[0059] The above description is only the best specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A method for treating surface-coated modified AlH3, characterized in that: The following steps are involved: S1, placing AlH3 in a mixed solvent, stirring, filtering, and vacuum drying at room temperature; S2, mixing the surface treatment agent and the dispersant evenly, stirring, to obtain a surface treatment liquid; S3, adding the AlH3 treated in step S1 to the surface treatment solution prepared in step S2, stirring, mixing evenly, then filtering under reduced pressure, washing with deionized water and anhydrous ethanol for multiple times, and drying to obtain surface-coated modified AlH3; The surface treatment agent in step S2 is at least one of nickel fluoride and / or nickel (II) fluoride hydrate.

2. The processing method according to claim 1, characterized in that The dispersant in step S2 is a mixture of water and one of the following organic solvents: tetrahydrofuran, acetone, acetonitrile, and ethanol; the pH value of the dispersant is between 6 and 8.

3. The processing method according to claim 2, characterized in that: The dispersant is formulated as follows: When it is water / tetrahydrofuran, the volume fraction of water is 30% to 50%; When it is water / acetone, the volume fraction of water is 20% to 50%; When it is water / acetonitrile, the volume fraction of water is 30% to 50%; When it is water / ethanol, the volume fraction of water is 30% to 50%.

4. The processing method according to claim 1, characterized in that: The mixed solvent in step S1 is a mixture of water and one of tetrahydrofuran, acetone and acetonitrile, and the volume fraction of water is 1% to 10%.

5. The processing method according to claim 1, characterized in that: The mass ratio of AlH3, surface treatment agent and dispersant is: (50-55) parts: (5-10) parts: (35-45) parts.

6. The processing method according to claim 1, characterized in that: The temperature conditions in steps S1 and S2 are both 20°C to 30°C; the stirring speed is controlled at 60 to 400 rpm and the stirring time is 1 hour; The temperature condition of step S3 is 20° C. to 30° C.; the stirring speed is controlled at 60 to 400 rpm, and the stirring time is 1.5 to 3 hours.

7. A surface-coated modified AlH3, characterized in that: Obtained by the treatment method described in any one of claims 1 to 6, the AlH3 particles are coated with an inorganic shell layer to form a core-shell structure, the thickness of the inorganic shell layer ranges from 10 nm to 60 nm; the particle size of the AlH3 particles ranges from 10 μm to 90 μm; the composition of the inorganic shell layer includes Ni(OH)2 and Al(OH)3F6.

8. Use of the surface-coated modified AlH3 obtained by the treatment method according to any one of claims 1 to 6 in butyl hydroxyl solid propellant and nitrate ester plasticized propellant.

9. The use according to claim 8, characterized in that The butyl hydroxyl solid propellant comprises the following components by weight: 10 to 20 parts of surface-coated modified AlH3, 4 to 10 parts of dioctyl sebacate, 8 to 12 parts of terminal hydroxy butadiene, 55 to 67 parts of ammonium perchlorate, 0.3 to 0.5 parts of curing agent, and 0.02 to 0.05 parts of curing catalyst; The nitrate plasticized propellant comprises the following components in parts by weight: 10 to 20 parts of surface-coated modified AlH3, 15 to 22.5 parts of a nitrate plasticizer prepared by mixing NG and BTTN in a mass ratio of 1:1, 5 to 7.5 parts of a polyazide glycidyl ether adhesive, 35 to 45 parts of an explosive, 15 to 20 parts of ammonium perchlorate, 0.3 to 0.5 parts of a curing agent, and 0.02 to 0.05 parts of a curing catalyst.

10. The use according to claim 9, characterized in that The curing agent is at least one of hexamethylene diisocyanate and toluene diisocyanate; the curing catalyst is triphenyl bismuth; and the explosive is at least one of hexachlorobenzene or octogenin.

Citation Information

Patent Citations

  • Thermal stability of aluminum hydride through use of stabilizers

    US3801707A

  • Particulate aluminum hydride with nitrocellulose coating suitable for use in solid propellants

    US3855022A

  • Surface coating method of AlH3, coated AlH3 and application thereof

    CN110921629A

  • ADN / AlH3 composite microsphere, preparation method and solid propellant containing microsphere

    CN112441863A